Pola Makan dan Aktivitas Fisik Penderita Diabetes Melitus Tipe II di RSUD Kota Salatiga - Marlyn Olivia Paknianiwewan; R.L.N.K Retno Triandhini; Gelora Mangalik (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Abstract Diabetes Mellitus Disease (DM) has become a public health problem in various countries including Indonesia. DM is a complex chronic disease characterized by increased glucose levels in the blood caused by impaired glucose metabolism resulting in abnormalities of insulin secretion or lack of insulin production even both. The triggering factor of type II DM disease is diet. Unhealthy diets such as following a western diet that is consuming fast food, fatty and high-calorie, by consuming foods or drinks containing sugar can also increase the risk of dm type II events. In addition to dietary patterns, physical activity is another factor that influences the incidence of type II DM. Sedentari behavior that has now become a modern public lifestyle increases the risk of dm type II. This study aims to identify the diet and physical activity of dm type II patients in Salatiga City Hospital. This type of research is descriptive quantitative with cross-sectional approach conducted in The Polyclinic of Salatiga City Hospital from September - November 2019 with the number of respondents as many as 100 people taken with purposive sampling techniques. The research instruments used were SQ – FFQ questionnaires for diet and GPAQ questionnaires for physical activity patterns. Conclusion: The dietary patterns of respondents with Type II DM in Salatiga City Hospital has not all consumed foods with a balanced nutrition pattern and physical activity in respondents doing more moderate physical activity. Keywords: Diabetes mellitus, dietary patterns, physical activity pattern.